Resilience and sustainability strategies of Malaysian homestay program during COVID-19 pandemic - Nor Hafizah Selamat,; Khoo, Suet Leng; Premalatha Karupiah,; Zaireeni Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 outbreak in late 2019 has impacted all nations, societies, and industries globally due to the closure of international borders and strict travel restrictions. As one of the community-based tourism activities that have been viewed as a tool to stimulate rural community development, the Malaysian homestay program is no exception. This paper aims to explore the COVID-19 impacts, to examine how the homestay operators strived to be resilient and to understand the sustainability strategies adopted by them in reviving the industry post-COVID-19. By using a resilience-based framework, in-depth interviews with 10 homestay operators, one (1) state tourism official, and three (3) Homestay Chairman of the local homestay tourism association were conducted. Findings revealed that COVID-19 has affected the homestay operators’ livelihoods, where they experienced a total loss of incomes due to booking cancellations and the complete halt of tourist arrivals. Operators began to re-visit their business models and mapped out the ‘new norms of hospitality by leveraging technology and social media to promote their businesses online.’ All these innovative strategies need to be undertaken collectively and therefore leadership and the formation of strong human resources proved to be the best solutions. Diversifying and venturing into other businesses as second income generation provides a safety net in sustaining their livelihoods. It is suggested that the creation of new business models and pragmatic community tourism policies will essentially determine the homestay program’s chances of survival, particularly during crisis or disaster, by transforming it into a much more sustainable form.